2009
DOI: 10.1016/j.molbiopara.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the mechanism of action of praziquantel

Abstract: Although praziquantel (PZQ) has been used to treat schistosomiasis for over 20 years its mechanism of action remains unknown. We have developed an assay based on the transcriptional response of Schistosoma mansoni PR-1 to heat shock to confirm that while 6-week post-infection (p.i.) schistosomes are sensitive to PZQ, 4-week p.i. schistosomes are not. Further, we have used this assay to demonstrate that in mice this sensitivity develops between days 37 and 40 p.i. When PZQ is linked to the fluorophore BODIPY to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 54 publications
7
117
0
1
Order By: Relevance
“…These studies revealing genes that might be evolved in aerobic metabolism and cytosolic calcium regulation, suggesting that schistosomes undergo a transcriptomic response similar to that seen during oxidative stress (74). Moreover, it was demonstrated that CamKII (calcium/calmodulin-dependent protein kinase type II) appears to play a key role in the mode of action of PZQ1 and hence might be considered a promising novel drug target (76,77).…”
Section: How Does Pzq Kill Schistosomes?mentioning
confidence: 93%
See 1 more Smart Citation
“…These studies revealing genes that might be evolved in aerobic metabolism and cytosolic calcium regulation, suggesting that schistosomes undergo a transcriptomic response similar to that seen during oxidative stress (74). Moreover, it was demonstrated that CamKII (calcium/calmodulin-dependent protein kinase type II) appears to play a key role in the mode of action of PZQ1 and hence might be considered a promising novel drug target (76,77).…”
Section: How Does Pzq Kill Schistosomes?mentioning
confidence: 93%
“…High-throughput transcriptomic approaches have been employed to address the refractory/susceptible nature of the developmental stages of schistosomes in terms of PZQ1 activity (73)(74)(75)(76)(77). These studies revealing genes that might be evolved in aerobic metabolism and cytosolic calcium regulation, suggesting that schistosomes undergo a transcriptomic response similar to that seen during oxidative stress (74).…”
Section: How Does Pzq Kill Schistosomes?mentioning
confidence: 99%
“…on May 9, 2018 by guest http://cmr.asm.org/ and its precise mechanism of action remains unknown (9). A recent study implicated myosin light chain as an alternative target of PZQ (71).…”
Section: Vol 23 2010 Schistosomiasis and The Three Gorges Dam 451mentioning
confidence: 99%
“…Today, public health campaigns in endemic regions focus on mass drug administration using the oral drug, praziquantel (PZQ) [3]. Although PZQ is fairly efficacious against the sexually mature forms of the parasite, it is often unable to kill juvenile schistosomes present in the human body [4]. Additionally, there is concern that with the intensive use of PZQ drug resistance could render PZQ ineffective; given that drug resistant strains can easily be selected in the laboratory [5] and field derived strains with reduced susceptibility have been described [6].…”
Section: Introductionmentioning
confidence: 99%